EKSPRESI REKREATIF ala ORANG MADURA PERSPEKTIF TEORI KONSTRUKTIVISME - Edi Susanto, Edi Susanto (Institut Agama Islam Negeri Madura)
Edi Susanto (Penulis, dosen STAIN Pamekasan, Jl. Raya Panglegur Km. 04 Pamekasan. dan mahasiswa Program Doktor Pascasarjana IAIN Sunan Ampel Surabaya e-mail: edihabermas@yahoo.co.id; 085230028648) Abstract This is article is to snapshot the creative expression of Madurese using constructivism approach. The expressions reveal strong religious values, on the other hand they stand oppositely against those values. The writer comes to a conclusion that the recreation pattern of Madurese exhibits a religious look tourism. In fact, It is only a reflection of avoidance of eschatological affiction. It does not touch élan-transformative religion. Kata-kata kunci ekspresi rekreatif, Madura, konstruktivisme